Turbocharging DBMS buffer pool using SSDs - Do, Jaeyoung; Zhang, Donghui; Patel, Jignesh M.; DeWitt, David J.; Naughton, Jeffrey F.; Halverson, Alan (International Conference on Management of Data, 2011)
Flash solid-state drives (SSDs) are changing the I/O landscape, which has largely been dominated by traditional hard disk drives (HDDs) for the last 50 years. In this paper we propose and systematically explore designs for using an SSD to improve the performance of a DBMS buffer manager. We propose three alternatives that differ mainly in the way that they deal with the dirty pages evicted from the buffer pool. We implemented these alternatives, as well another recently proposed algorithm for this task (TAC), in SQL Server, and ran experiments using a variety of benchmarks (TPC-C, E and H) at multiple scale factors. Our empirical evaluation shows significant performance improvements of our methods over the default HDD configuration (up to 9.4X), and up to a 6.8X speedup over TAC.